Cambridge practice tests for first certificate 2 - Carne, Paul (Cambridge Univ. Press, 1996)
Contains four complete tests for the First Certificate exam from Cambridge ESOL. These past examination papers provide the most authentic exam preparation available, allowing candidates to familiarise themselves with the content of the exam and to practise exam techniques. Colour visual material for Paper 5 is included with each test. The Student's Book is also available as a 'with answers' edition, suitable for self study